Evaluation of Completeness of Cancer Data Variables on Data Quality in Hospital-Based Cancer Registration Activities at Dharmais Cancer Hospital - Shalmont, Grace; Rahayu, Pradnya Sri; Hutajulu, Susanna Hilda; Lazuardi, Lutfan (Rumah Sakit Akademik Universitas Gadjah Mada, 2023)
Background: Cancer is a major burden of disease worldwide, including in Indonesia. As an effort to control the burden of cancer, WHO established National Cancer Control Programs (NCCP) where cancer registration is one of the key points. Dharmais Cancer Center Hospital, appointed as the national cancer center, has the responsibility to conduct a cancer registry in Indonesia. The good quality data of cancer registry according to international standards is beneficial to describe the cancer burden in the country. In Dharmais Cancer Center Hospital, microscopic verification is one of the variables that has not been qualified. Therefore, it is important to evaluate the completeness of cancer data variables toward data cancer quality on hospital-based cancer registry of Dharmais Cancer Center Hospital. To assess the quality of cancer data based on microscopic verification, to evaluate the completeness of hospital-based cancer registry variables and the quality of data based on microscopic verification between complete and incomplete variable groups. Materials and Methods: This quantitative research is an observational study (non-experimental) with cross-sectional study design. It utilizes secondary data from hospital-based cancer registry of Dharmais Cancer Center Hospital for incidence year 2013-2017.Results: Data quality of microscopic verification that assessed on a complete data group is 87,8% and for overall cancer cases is 62%. Among social variables, identity numbers are the most incomplete variable, which is 39%. While among tumor data variables, stage is also the most incomplete variable with 82% data. There are differences between the quality of data based on microscopic verification with the completeness of data, especially among social data variables and tumor data variables. Conclusion: The quality data based on microscopic verification that is assessed on a complete variable group is better than microscopic verification on overall cancer cases. The incomplete variables among social variables are identity number, date of birth, address, and district/province. Whereas on tumor variables, the incomplete variables are stage, treatment, metastasis, and laterality. The completeness of cancer data has an importantrole on data quality based on microscopic verification mainly on social and tumor variables. Improvement and strengthening particularly on management and technical aspects of cancer registration are indispensable